Assessing the viability of cryopreserved coconut zygotic embryos by electrolytic conductivity and potassium leaching - Kicia Karinne Pereira Gomes-Copeland; Ana da Silva Lédo; Fabrício Tavares Cunha de Almeida; Roberta Pereira Miranda; Izulmé Rita Imaculada Santos (Pesquisa Agropecuária Brasileira, 2012)
The objective of this work was to adapt the application of electrolytic conductivity and potassium leaching tests to assess the viability of cryopreserved embryos of 'Anão Verde do Brasil de Jiqui' (AVeJBr) coconut. The zygotic embryos were excised, sterilized and subjected to four cryoprotectant treatments combined with three incubation times (12, 16 and 20 hours), totaling 12 treatments. The pre-treatment of mature zygotic embryos of AVeJBr coconut using a cryoprotectant with 1.75 mol L-1 of sucrose + 15% glycerol for 12 and 16 hours promoted lower embryo humidity and increased viability in electrolytic conductivity and potassium leaching tests. Samples with ten embryos are sufficient for electrolytic conductivity analysis in cryopreserved or non-cryopreserved AVeJBr coconut zygotic embryos. The 4 to 8 hour imbibition period of the embryos is promising for the electrolytic conductivity analysis of non-cryopreserved mature zygotic embryos of AVeJBr coconut.